Sustainable initiatives in the food industry: Role of businesses and regulators - Geoffrey Tanakinjal (LLC "CPC "Business Perspectives", 2021)
In response to global calls for environmental awareness, the Malaysian government enforced restrictions on plastic usage in the Malaysian foodservice industry in 2020. Despite the efforts of public awareness campaigns championing the detrimental effects of traditional plastic usage, the impact of measures taken by food traders remains inadequate. The paper seeks to explore the relationship between subjective norms, perceived behavioral control, attitude, and the intention to use biodegradable straws among food traders. Purposive sampling method, the Structural Equation Model (SEM), and Partial Least Squares (PLS) tools were employed. The sample included 270 respondents. The result found a significant correlation between the four variables, i.e., subjective norms, perceived behavioral control, attitude, and intention to use. Hence, results obtained indicate that conscientious consumers have a significant influence on businesses in their quest to reduce their overall impact on the surrounding environment. Consequently, their socially responsible decisions, i.e., initiatives of using biodegradable products, have advocated mindful consumerism and encouraged positive purchasing behaviors. The results predict increasing demands as an outcome of this accumulated synergy, and this in turn provides more opportunities for food traders and their associated counterparts. The contributions of this study extend toward both theoretical and practical knowledge: (a) better understanding of consumer attitude and how it influences purchase intention, and (b) government regulation and enforcement towards environmental awareness and activities associated with global contributions.